Retrograde intubation through nasal route in patients with limited mouth opening undergoing oral and maxillofacial surgery - Ashwant Kumar Vadepally; Ramen Sinha; A.V.S.S. Subramanya Kumar (Journal of Oral Biology and Craniofacial Research)
Background: Patients with limited mouth opening (LMO) often associated with difficult intubation. Retrograde intubation is an alternative technique of establishing definitive airway in these patients when blind nasal intubation fails and fiberoptic bronchoscope is not available. We tested the retrograde intubation through nasal route in patients with LMO less than 2 cm. Materials and methods: The procedure was performed with some modification with regard to retrograde guide on 18 patients requiring maxillofacial surgical procedures to increase mouth opening. Indications for this technique were mandibular fracture (n = 6), oral submucous fibrosis (OSMF; n = 6), temporomandibular joint (TMJ) ankylosis (n = 4) and internal derangement of TMJ (n = 2). All patients were assessed for preoperative interincisal opening; during intubation through specific parameters and; also postoperative findings were observed. Results: Mean time taken for successful intubation was 5.6 min ± 1.66. One patient had subcutaneous emphysema which was managed conservatively. Postoperatively, four patients had sore throat which resolved in few days. No other complications were encountered. Conclusion: In conclusion, retrograde nasotracheal intubation is an effective and useful technique for airway control in patients with LMO and with only a small risk potential.